Balancing risks of injury and disturbance to marine mammals when pile driving at offshore windfarms. Issue 2 (29th November 2020) - Thompson, Paul M.; Graham, Isla M.; Cheney, Barbara; Barton, Tim R.; Farcas, Adrian; Merchant, Nathan D.
Abstract: 1. Offshore windfarms require construction procedures that minimize impacts on protected marine mammals. Uncertainty over the efficacy of existing guidelines for mitigating near‐field injury when pile‐driving recently resulted in the development of alternative measures, which integrated the routine deployment of acoustic deterrent devices (ADD) into engineering installation procedures without prior monitoring by marine mammal observers. 2. We conducted research around the installation of jacket foundations at the UK's first deep‐water offshore windfarm to address data gaps identified by regulators when consenting this new approach. Specifically, we aimed to (a) measure the relationship between noise levels and hammer energy to inform assessments of near‐field injury zones and (b) assess the efficacy of ADDs to disperse harbour porpoises from these zones. 3. Distance from piling vessel had the biggest influence on received noise levels but, unexpectedly, received levels at any given distance were highest at low hammer energies. Modelling highlighted that this was because noise from pin pile installations was dominated by the strong negative relationship with pile penetration depth with only a weak positive relationship with hammer energy. 4. Acoustic detections of porpoises along a gradient of ADD exposure decreased in the 3‐h following a 15‐min ADD playback, with a 50% probability of response within 21.7 km. The minimum time to the first porpoise detection after playbacks was > 2 h for sites within 1 km of the playback. 5. Our data suggest that the current regulatory focus on maximum hammer energies needs review, and future assessments of noise exposure should also consider foundation type. Despite higher piling noise levels than predicted, responses to ADD playback suggest mitigation was sufficiently conservative. Conversely, strong responses of porpoises to ADDs resulted in far‐field disturbance beyond that required to mitigate injury. We recommend that risks to marine mammals can be further minimized by (1) optimizing ADD source signals and/or deployment schedules to minimize broad‐scale disturbance; (2) minimizing initial hammer energies when received noise levels were highest; (3) extending the initial phase of soft start with minimum hammer energies and low blow rates. Abstract : Offshore windfarms require procedures that minimise impacts of construction noise on protected marine mammals. Unexpectedly, our studies at the UK's first deep‐water offshore windfarm revealed that underwater noise levels were highest at the start of piling, rather than at maximum hammer energy. We observed strong responses of harbour porpoises to acoustic deterrent devices (ADD) deployed prior to piling, resulting in far‐field disturbance beyond that required to mitigate injury. These results highlight that risks to marine mammals can be further minimised by optimising ADD source signals and/or deployment schedules to minimise broad‐scale disturbance and minimising initial hammer energies when received noise levels were highest.